Membranes: Combining Phosphate and Bacteria Removal on Chemically Active Filter Membranes Allows Prolonged Storage of Drinking Water (Adv. Mater. 42/2013). (November 2013) - Rotzetter, A. C. C.; Kellenberger, C. R.; Schumacher, C. M.; Mora, C.; Grass, R. N.; Loepfe, M.; Luechinger, N. A.; Stark, W. J.
<x xml:space="preserve">Abstract</x> On page 6057, W. J. Stark and co‐workers present a chemically active filtration membrane that removes bacteria and the essential growth nutrient phosphate in a single filtration step. This allows the suppression of the microbial regrowth processes and thus, provides a simple device for the preparation of drinking water and subsequent safe storage. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>